Términos impropios en el lenguaje científico-médico - Hernández de la Rosa, Yurima; Martínez Méndez, Nora; Gil Hernández, Tunia; Ramos Costa, María I.; López Díaz, Lídice; Vasconcelos Ramírez, Dudiexi (CorSalud, 2013)
Términos impropios en el lenguaje científico-médico